2007
DOI: 10.1007/s00420-007-0282-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported symptoms and consequences related to inhalation of airborne chemicals in a Danish general population

Abstract: Symptoms related to inhalation of airborne chemicals were common in this general population, and a minority reported that these symptoms affected social life or occupational conditions. Women as compared to men reported more symptoms but not adjustments of social life or occupational conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 15 publications
3
93
0
Order By: Relevance
“…According to population-based surveys, the prevalence of MCS is estimated to range from 8 to 33 % [4][5][6][7][8][9]. Thus, MCS has become a large public health concern during the past two decades, particularly in industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
“…According to population-based surveys, the prevalence of MCS is estimated to range from 8 to 33 % [4][5][6][7][8][9]. Thus, MCS has become a large public health concern during the past two decades, particularly in industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
“…Group 1 participants were respondents to a population-based cross-sectional survey (n = 4260) randomly drawn from the Danish Civil Registration System [34]. Respondents (n = 1134) were invited to participate in the study providing they had (1) reported being bothered by exposure to at least one chemical (e.g., fragranced products, newly printed magazines); (2) confirmed that such exposure was associated with symptoms and not perceived as merely unpleasant; (3) given consent to be contacted again (n = 787).…”
Section: Participantsmentioning
confidence: 99%
“…IEI was assessed by (1) number and severity of 20 symptoms used in a previous Danish population-based study on the prevalence of symptoms attributed to common airborne chemicals [34], including headache, exhaustion, dizziness, difficulties concentrating, grogginess, sleep difficulties, panic attacks, breathlessness, symptoms from the eyes, nose, sinuses, mouth, throat and lungs; (2) number of symptom-inducing airborne chemicals, including fragranced products, cleaning agents, nail polish remover, newly printed papers or magazines, new furniture, soft plastic or rubber, cooking fumes, motor vehicle exhaust, tar or wet asphalt, smoke from a wood burner and new electric equipment; (3) social consequences that were assessed by the following question: ''Do reactions caused by environmental odours lead you to avoid'': (a) social activities (e.g., family or other private parties), (b) inviting guests, (c) going on holiday, (d) sports activities, (e) using public transportation, (f) going to the cinema or theatre (g) going to restaurants? were severely affected.…”
Section: Measurementsmentioning
confidence: 99%
“…Many individuals in the general population report symptoms related to inhalation of airborne chemicals (Berg et al 2008;Caress and Steinemann 2003;Caress and Steinemann 2004;Carlsson et al 2005; Centre for Epidemiology and Research 2003;Hausteiner et al 2005;Johansson et al 2005;Kreutzer et al 1999;Meggs et al 1996;Park and Knudson 2007), and in a minority of more severely aVected individuals these symptoms are reported to aVect social life or occupational conditions (Berg et al 2008;Caress and Steinemann 2003;Caress and Steinemann 2004;Kreutzer et al 1999).…”
Section: Introductionmentioning
confidence: 97%